Cracking‐Controlled Slurry Coating of Mosaic Electrode for Flexible and High‐Performance Lithium–Sulfur Battery. Issue 3 (27th November 2022) - Luo, Yufeng; Wang, Lei; Wei, Zhenyao; Huang, Qiyao; Deng, Yonghong; Zheng, Zijian
Abstract: The realization of high‐performance thick S cathodes is a critical step to achieve high energy density lithium–sulfur (Li–S) batteries. However, it normally requires a complicated and time‐consuming fabrication processes to obtain high‐performance S cathodes with high mass loading. On the other hand, thick S cathodes fabricated with high‐speed slurry coating method show poor flexibility, capacity, and cycle life due to unpredictable electrode cracking. Herein, an industrial‐speed cracking‐controlled slurry coating method to generate mosaic‐like cracks in the S cathode is developed, which provides vertical channels to facilitate the rapid diffusion of electrolyte, adequate space to accommodate the volume expansion during cycling, and strain‐releasing structure to achieve high flexibility. With this simple method, thick Mosaic‐S cathodes (9 mAh cm −2 ) provide outstanding energy density, long cycle life, and outstanding flexibility under dynamic bending. This work paves the way for scalable fabrication of high‐performance S cathodes in the near future. Abstract : A cracking‐controlled slurry coating method to fabricate flexible mosaic‐like electrodes is reported. The regular preformed cracks in the Mosaic‐S cathode can facilitate electrolyte diffusion, provide enough space to accommodate volume expansion during cycling, and enable a strain‐releasing structure to achieve outstanding electrochemical performance and flexibility of lithium–sulfur batteries.